The Everyday Resilience of the City - Coaffee, J. author. aut Link
XI, 341 p.
Keywords: This book examines the practice of urban resilience past and present, drawing on deeper global historical sources and detailed case-studies of contemporary Britain. It argues that resilience is neither new nor necessarily about protecting ordinary people, but part of a long struggle over the control of cities.